ANALISIS PENGARUH BEBAN KERJA FISIK MENGGUNAKAN METODE RULA REBA DAN BIOMEKANIKA TERHADAP PRODUKTIVITAS KERJA BAGIAN DEPARTEMEN MEKANIKA DI PT.XYZ - Ayu Fitrianingsih, - (2019)
The Commuter Trains of PT Indonesia (KCI) is a subsidiary of PT Kereta Api environment in Indonesia (Persero) which manages the Jabodetabek Commuter RAILWAY and surrounding areas. KCI Begin modernizing transport KRL in 2011 by simplifying existing routes into five main routes, the Elimination of KRL, the application of a special train women, and change the name of KRL economy into a Commuter train Line. Work activity in Indonesia, PT Commuter Train mechanics also are demanding workload because most of his work is still a manual or still using human power. Hence the need for research on the influence of workload against the level of productivity of work. Measurement of the workload by using method of RULA, method of REBA and method of Biomekanika, while for the measurement of psychological workload by using methods of the NASA TLX. Further analysis conducted of the relationship between the workload against the employee work productivity of mechanics by using SPSS software using test R-Square, F-test, kolineritas test, multiple linear regression testing, simple linear regression test. The results of calculation show that there is still a Division with the level of physical and mental workload is high and medium. Results processing with SPSS software for a series of statistical tests is the existence of a significant relationship between workload against work productivity levels of workers. The observations about the safety of the working environment and occupational health, still there are employees who disregard the equipment work. Observations on sustainable manufacturing waste handling and improved welfare for employees and the surrounding communities